2010
DOI: 10.1111/j.1748-5827.2010.00989.x
|View full text |Cite
|
Sign up to set email alerts
|

Population characteristics and survival in 127 referred cats with hypertrophic cardiomyopathy (1997 to 2005)

Abstract: Objectives: To evaluate the characteristics and survival of a recent population of cats with hypertrophic cardiomyopathy. Methods: Records at the Royal Veterinary College Queen Mother Hospital for Animals were searched for cats diagnosed with hypertrophic cardiomyopathy between 1997 and 2005. Referring veterinarians and owners were contacted to determine survival times. Results: Cats with hypertrophic cardiomyopathy were evaluated for population characteristics (n=127) and survival times (n=109). Overall m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
144
9
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(191 citation statements)
references
References 15 publications
29
144
9
9
Order By: Relevance
“…Median survival time for cats with CHF in the current study is similar to that reported in previous studies, which ranges from 41 to 626 days 35, 36, 37, 38, 39, 40, 41, 42, 43. There were no associations between medications (including pimobendan) and survival time in the current study, which is likely due to the relatively small sample size and the fact that cats were receiving multiple medications.…”
Section: Discussionsupporting
confidence: 88%
“…Median survival time for cats with CHF in the current study is similar to that reported in previous studies, which ranges from 41 to 626 days 35, 36, 37, 38, 39, 40, 41, 42, 43. There were no associations between medications (including pimobendan) and survival time in the current study, which is likely due to the relatively small sample size and the fact that cats were receiving multiple medications.…”
Section: Discussionsupporting
confidence: 88%
“…The clinical and prognostic value of LA size (determined echocardiographically) in cats with HCM has been repeatedly demonstrated, and thus is often used as a clinical surrogate of clinical severity and hemodynamic burden 5, 19, 31, 32, 33, 34. In our study, LV free wall thickness, RV chamber size, and RV function (as assessed by 2D TAPSE) were independently correlated with LA size.…”
Section: Discussionsupporting
confidence: 52%
“…As reported by other authors, a male bias was evident in our population of cats with ATE 4, 6, 7, 8. Hypertrophic cardiomyopathy also has a male sex predisposition,9, 10, 11, 15, 16 which may explain the male bias in cats with ATE. The pedigree breeds reported here are also over‐represented in reported descriptions of cardiomyopathy in cats 10, 11, 15…”
Section: Discussionmentioning
confidence: 99%
“…These data were obtained from cats treated in referral practice and do not necessarily represent the general feline population. Feline ATE is most commonly associated with cardiomyopathy, although cardiac disease is not present in all affected cats 4, 5, 6, 7, 8, 9, 10, 11, 12, 13…”
mentioning
confidence: 99%